Location of the euryon in scaphocephalic vs. non-scaphocephalic controls: A novel assessment of cranial vault remodeling outcomes. Issue 4 (April 2018) - Winters, Ryan; Tatum, Sherard A.
Abstract: We describe a novel measurement of cranial morphology in pre- and post-operative scaphocephalic patients to complement the cephalic index. This will better describe restoration of normal skull and head shape, further defining the nuances of the corrected skull. In this retrospective comparative study the location of the euryon on the skull was statistically significantly different in preoperative scaphocephalic patients versus non-scaphocephalic controls. This difference was resolved with surgical cranial vault remodeling, indicating restoration of a normal skull profile. Additional measurements of the location of the euryon in relation to the forehead prominence, combined with validated cephalic index measurements, can further describe postoperative outcomes in scaphocephaly. More sensitive clinical measurements such as these can aid the craniofacial surgeon in assessing outcomes in cranial vault remodeling. Further, large-scale study is needed to determine if additional anterior skull metric points may be useful in documenting skull shape restoration.